Digital Counter-Radicalism: The Strategic Role of Religious Organisations in Shaping Moderate Islam in Indonesia’s Cyber Realm - Dadang Kuswana (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study investigates the digital strategies employed by Nahdlatul Ulama (NU) and Muhammadiyah, two of Indonesia's largest moderate Islamic organisations, in countering radicalism on social media. The research aims to evaluate the effectiveness of these strategies in reaching and influencing the younger generation, particularly in the context of growing radical content online. Methodology: A qualitative approach was utilised, involving direct observation of social media content, in-depth interviews with key figures from NU and Muhammadiyah, and a review of relevant literature. The study also included interviews with Generation Z students to gauge their responses to the digital strategies of these organisations. Findings: The study found that NU's innovative approach, particularly through creative social media campaigns like